2022
DOI: 10.1002/ajmg.a.62745
|View full text |Cite
|
Sign up to set email alerts
|

A patient with a novel pathogenic variant in COL5A1 exhibiting prominent vascular and cardiac features

Abstract: The Ehlers–Danlos Syndromes (EDS) are a group of inherited connective tissue disorders with a worldwide prevalence of 1 in 2500 to 1 in 5000 births irrespective of sex or ethnicity. Fourteen subtypes of Ehlers–Danlos Syndrome (EDS) have been described, each with characteristic phenotypes and associated genes. Pathogenic variants in COL5A1 and COL5A2 cause the classical EDS subtypes. Pathogenic variants in COL3A1 cause vascular EDS. In this case report, we describe a patient with a phenotype resembling that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Lavanya et al (2022) described a male with an overlapping cEDS/vEDS phenotype with a COL5A1 frameshift c.2892_2893delCCinsT p.P966LfsX108 variant in exon 36. Physical examination revealed translucent skin, acrogeria, easy bruising, thin vermilion of the lips, narrow nose, prominent eyes and hypermobility of multiple joints.…”
Section: Other Vascular Ehlers Danlos Syndrome-like Phenotypesmentioning
confidence: 99%
“…Lavanya et al (2022) described a male with an overlapping cEDS/vEDS phenotype with a COL5A1 frameshift c.2892_2893delCCinsT p.P966LfsX108 variant in exon 36. Physical examination revealed translucent skin, acrogeria, easy bruising, thin vermilion of the lips, narrow nose, prominent eyes and hypermobility of multiple joints.…”
Section: Other Vascular Ehlers Danlos Syndrome-like Phenotypesmentioning
confidence: 99%
“…with a novel pathogenic variant in COL5A1 exhibiting prominent vascular and cardiac features" (Lavanya et al, 2022) that describes a patient with a phenotype reminiscent of vascular Ehlers-Danlos Syndrome (EDS) and was found to have a novel pathogenic variant in COL5A1 (c.2892_2893delCCinsT, [p.Pro1127HisfsTer149]), along with a review of genetic variants in COL5A1 in reports with significant vascular abnormalities. Our group has previously reported that a recurrent variant c.1540G>A, (p.Gly514Ser) in COL5A1 was associated with a vascular phenotype inclusive of arterial dissections and multifocal fibromuscular dysplasia (FMD) (Richer et al, 2020).…”
mentioning
confidence: 99%